ANALYSIS OF CUSTOMER LOYALTY MODELS INFLUENCED BY CUSTOMER RELATIONSHIP MANAGEMENT AND SATISFACTION IN TRANSPORTATION SERVICES - Raihanah Daulay (AIBPM Publisher, 2022)
Transportation services are a much needed need today. But the pandemic has caused all sectors to experience a tremendous decline, including transportation. efforts are needed to retain existing customers to remain loyal to using transportation services with a customer relationship management strategy. This study determined how satisfaction and customer relationship management affect client loyalty. The participants in this study are people who have used online cab transportation services for more than two years in Medan that was started by 85 different people. An online survey that had been verified for validity and reliability was used in the data collection process. The data analysis method employed traditional assumption testing, hypothesis testing, and multiple linear regression. The findings indicate that, in part, customer relationship management and satisfaction have a major impact on customer loyalty, and that, in part, customer relationship management and satisfaction have a substantial impact on customer loyalty for online cab transportation services